Ethylhexyl methoxycinnamate and butyl methoxydibenzoylmethane: Toxicological effects on marine biota and human concerns. Issue 1 (7th June 2021) - da Silva, Anne C. P.; Santos, Bianca A. M. C.; Castro, Helena C.; Rodrigues, Carlos R.
Abstract: Ethylhexyl methoxycinnamate (EHMC) (CAS number: 5466‐77‐3) and butyl methoxydibenzoylmethane (BMDM) (CAS number: 70356‐09‐1) are important sunscreens. However, frequent application of large amounts of these compounds may reflect serious environmental impact, once it enters the environment through indirect release via wastewater treatment or immediate release during water activities. In this article, we reviewed the toxicological effects of EHMC and BMDM on aquatic ecosystems and the human consequences. According to the literature, EHMC and BMDM have been detected in water samples and sediments worldwide. Consequently, these compounds are also present in several marine organisms like fish, invertebrates, coral reefs, marine mammals, and other species, due to its bioaccumulation potential. Studies show that these chemicals are capable of damaging the aquatic beings in different ways. Further, bioaccumulation studies have shown that EHMC biomagnifies through trophic levels, which makes human seafood consumption a concern because the higher position in the trophic chain, the more elevate levels of ultraviolet (UV) filters are detected, and it is established that EHMC present adverse effects on the human organism. In contrast, there are no studies on the BMDM bioaccumulation and biomagnification potential. Different strategies can be adopted to avoid the damage caused by sunscreens in the environment and human organism. Two of them include the use of natural photoprotectors, such as polyphenols, in association with UV filters in sunscreens and the development of new and safer UV filters. Overall, this review shows the importance of studying the impacts of sunscreens in nature and developing safer sunscreens and formulations to safeguard marine fauna, ecosystems, and humans. Abstract : Frequent application of large amounts of ethylhexyl methoxycinnamate (EHMC) and butyl methoxydibenzoylmethane (BMDM) may reflect serious environmental impact, once it enters the environment through indirect release via wastewater treatment or immediate release during water activities. In this article, we reviewed the toxicological effects of EHMC and BMDM on aquatic ecosystems and the human consequences. This review shows the importance of studying the impacts of sunscreens in nature and developing safer sunscreens and formulations to safeguard marine fauna, ecosystems, and humans.